Effectiveness of the Implementation of the Dispute Resolution Information System (SIPS) of the General Elections Supervisory Agency - Uswatun Hasanah; Anshory Ilyas; Zulkifli Aspan (IHSA Institute, 2022)
The main problems in this study are 1) How Effective is the Implementation of the Dispute Resolution Information System (SIPS) of the General Elections Supervisory Agency?, and 2) What are the efforts made by the Bawaslu of South Sulawesi Province in increasing the effectiveness of the Dispute Resolution Information System (SIPS)?. This study aims to determine the effectiveness of the implementation of the Dispute Resolution Information System in Bawaslu, especially in South Sulawesi, and to find out how the efforts made by the Bawaslu of South Sulawesi Province in increasing the effectiveness of the Dispute Resolution Information System (SIPS). This type of research is empirical or often referred to as social legal research, namely research conducted with an approach to the legal reality in society. The research location is South Sulawesi Province, in particular at the office of the General Elections Supervisory Agency (Bawaslu) of South Sulawesi Province, which is located at Jl. Andi Prince Pettarani No. 98A, Makassar, South Sulawesi Province. The research population of the Bawaslu of South Sulawesi Province, the General Election Commission of South Sulawesi Province, Political Parties in the South Sulawesi Province, Academics in the South Sulawesi Province, and the People of South Sulawesi Province. Respondents were determined as many as 60 people. Data was collected through observation, questionnaires and interviews. The data were analyzed using a qualitative approach. The results showed: 1) Whereas the Implementation of the Effectiveness of the Dispute Resolution Information System (SIPS) of the General Elections Supervisory Body, especially in the Bawaslu area of ??South Sulawesi Province, is not running effectively; 2) Whereas the efforts made by the Bawaslu of South Sulawesi Province in increasing the effectiveness of the Dispute Resolution Information System (SIPS), namely increasing the Resources of the Organizing Apparatus, facilities and infrastructure, the role of the Community, and Legal Substance. The suggestions put forward are: 1) It is necessary to strengthen and improve the legal substance of the technical implementation of dispute resolution requests through SIPS in the next election by maximizing the implementation of socialization and technical guidance to stakeholders and external parties regarding the procedures and procedures for requesting disputes;